1982
DOI: 10.1530/jrf.0.0650111
|View full text |Cite
|
Sign up to set email alerts
|

Preovulatory follicular development in sheep treated with PMSG and/or prostaglandin

Abstract: The patterns of growth and atresia of antral follicles including that of the presumptive preovulatory follicle were examined in sheep ovaries for a 24\p=n-\48-h period after the induction of luteolysis with a prostaglandin analogue, cloprostenol or cloprostenol + PMSG. Ewes were ovariectomized at various times after the initiation of the treatments. All follicles \m=ge\1 mm in diameter were dissected from the excised ovaries and the antral fluid and granulosa cells recovered. Individual follicles were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0
6

Year Published

1984
1984
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 25 publications
6
46
0
6
Order By: Relevance
“…The present findings on absolute numbers of granulosa cells per preovulatory follicle are consistent with the data of McNatty et al (1982), in which granulosa cell numbers were counted in a haemocytometer after mechanical dislodgement from the walls of follicles from Romney ewes treated with cIoprosteno!. These authors derived a formula to express the relationship between maximum number of recoverable granulosa cells and follicular diameter, and observed a maximum of :::: 10 X 10 6 granulosa cells in follicles of the largest sizes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present findings on absolute numbers of granulosa cells per preovulatory follicle are consistent with the data of McNatty et al (1982), in which granulosa cell numbers were counted in a haemocytometer after mechanical dislodgement from the walls of follicles from Romney ewes treated with cIoprosteno!. These authors derived a formula to express the relationship between maximum number of recoverable granulosa cells and follicular diameter, and observed a maximum of :::: 10 X 10 6 granulosa cells in follicles of the largest sizes.…”
Section: Discussionsupporting
confidence: 91%
“…This is particularly true when follicles need to be processed intact for morphological studies, eliminating the possibility of functional studies on the follicular cells or of analysis of follicular fluid, which could provide additional evidence of preovulatory status (McNatty et al 1982;Webb and England 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The close correlation between the number of healthy by PMSG. This result is supported by the findings that the number of follicles > 1 mm is unchanged after PMSG administration (McNatty et al, 1982) while the number of follicles >2 mm increases (Dott et al, 1979). Follicles recruited by PMSG are much smaller than those recruited at luteolysis of an unstimulated cycle to undergo preovulatory enlargement ( > 2 mm: Driancourt & Cahill, 1984;Tsonis et al, 1984).…”
Section: Discussionmentioning
confidence: 79%
“…during luteolysis. Other evidence suggests that the final selection of the ovarian follicle(s) destined to ovulate is from a pool of small follicles (2-4 mm diameter) present at the time of luteolysis (Smeaton & Robertson, 1971;Bhérer, Dufour & Matton, 1976;McNatty, 1982;McNatty et al, 1982). made because the extraction efficiency was in the range of 90-95%.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis. The LH surge was defined as when LH was > 10 ng/ml for > 6 h, and the onset when concentrations first exceeded 10 ng/ml (Wright, Geytenbeek, Clarke & Findlay, 1980 (Smeaton & Robertson, 1971 ;Bhérer et al, 1976;McNatty, 1982;McNatty et al, 1982) Smeaton & Robertson (1971) observed that, in 1 ewe of 7 studied, 2 medium-large follicles marked with ink on Day 13 subsequently ovulated. Bhérer et al (1976) observed that while the largest follicle marked on Day 14 subsequently ovulated, when there were twin ovulations the second ovulation resulted from a smaller unmarked follicle.…”
Section: Introductionmentioning
confidence: 99%